Evaluation of Rhizobia strains UFLA 02 100 and CIAT 899 in line LEP 02 11 of Phaseolus vulgaris L. (Bioscience Journal, 2019)
The growing quest for sustainability in agricultural production systems has been pushing researchers to develop new technologies under different soil and climatic conditions. Based on this, and knowing the socioeconomic importance of the bean, the use of biological nitrogen fixation (BNF) is explored. Thus, the quest for quantitative knowledge of BNF at the phenological stages in a new bean line using promising and commercial strains becomes necessary. The objective of this study was to evaluate the strains UFLA 02 100 and CIAT 899 in the different phenological stages of the LEP 02 11 common bean strain using the biological nitrogen fixation. The experiment was conducted in a greenhouse on the Maringá-PR campus of the State University of Maringá. The design was a randomized complete block design in a 6x4 factorial scheme with four replications. The factor A comprised six nitrogen sources: Control, strain UFLA 02 100, strain CIAT 899, Nitrogen 60 kg ha-1, strain UFLA 02 100 + Nitrogen 30 kg ha-1, strain CIAT 899 + Nitrogen 30 kg ha-1 and the B factor is the phenological stages V4, R5, R6 and R8. The analyzed variables were: dry mass of nodules (DMN, grams/plant), dry mass of shoot (DMS, grams/plant), nitrogen content in shoot (NCS, %) and accumulation of nitrogen in shoot (ANS, grams/plant). For the statistical analysis of the data, the means test was used for the variables in the stages. The CIAT 899 strain statistically outperformed UFLA 02 100 for most variables and it was found that nitrogen fertilization negatively affected nodulation.